Murine models of Staphylococcus aureus biofilm infections and therapeutic protein A vaccination - Walton, Kelly D., author; Kendall, Lon V., advisor; Dow, Steve W., advisor; Ryan, Elizabeth, committee member (Colorado State University. Libraries, 2013)
Staphylococcus aureus is a leading cause of nosocomial and community-acquired infections, and the appearance of antimicrobial resistance continually presents new treatment challenges. In addition, S. aureus is a biofilm-producing pathogen that is commonly implicated in implant-associated infections. Biofilm formation represents a unique mechanism by which S. aureus and other microorganisms are able to avoid antimicrobial clearance and establish chronic infections, and these infections are characteristically refractory to standard antimicrobial therapy. There is a great need for the development of effective animal models for the study of biofilm infections and novel therapeutics. There is also substantial interest in the utilization of noninvasive, in vivo data collection techniques to reduce animal numbers required for the execution of infectious disease studies. To address these needs, we evaluated three murine models of implant-associated biofilm infection using in vivo bioluminescent imaging (BLI) techniques. The goal of these studies was to identify the model that was most amenable to development of sustained infections which could be repeatedly imaged in vivo using BLI technology. We found that a subcutaneous (s.c.) mesh and a tibial intramedullary (i.m.) pin model both maintained consistent levels of bioluminescence for up to 35 days post-infection, with no implant loss experienced in either model. In contrast, a s.c. catheter model demonstrated significant incidence of incisional abscessation and implant loss by day 20 post-infection. The correlation of bioluminescent measurements and bacterial enumeration was strongest with the s.c. mesh model whereas the correlation was weaker with the i.m. pin model. These data suggest that the s.c. mesh model is the most appropriate animal model of the three evaluated for the prolonged study of biofilm infections using BLI. Vaccination has been proposed as a potential therapeutic strategy for chronic staphylococcal infections; however recent attempts to develop an effective vaccine have been met with marginal success. One of the most important virulence factors of S. aureus is the membrane-bound protein Staphylococcal Protein A (SpA), which functions to inhibit both the innate and adaptive immune responses of the host. The majority of clinically relevant strains of S. aureus express SpA, making this protein a natural target for novel immunotherapeutics. A nontoxigenic form of SpA was previously developed, and prophylactic immunization with the protein was shown to promote innate and adaptive immune responses that are protective against disease in a mouse model of S. aureus bacteremia. This recent discovery further suggests that neutralization of SpA may improve clinical outcomes of staphylococcal infection. In the present study, we sought to determine the value of therapeutic vaccination targeting SpA for treatment of S. aureus biofilm infections. Our findings demonstrated that mice treated with repeated SpA vaccination following subcutaneous placement of S. aureus-coated mesh implants did not exhibit improved bacterial clearance when compared with untreated mice, although a strong humoral immune response to vaccination was observed. Using in vivo bioluminescent imaging, we also showed that the bacterial burden remained consistent between the vaccinated and unvaccinated groups of animals over the course of the study period. Furthermore, in vitro assays demonstrated that antibodies against SpA did not bind effectively to S. aureus, however opsonophagocytic clearance of planktonic bacteria was enhanced in the presence of whole blood from immunized mice. While these results suggest that SpA vaccination was not an effective tool for the treatment of S. aureus biofilm infections, more research is necessary to determine the specific role of SpA in biofilm development and other non-SpA mechanisms that are responsible for biofilm resistance.
Keywords: animal models; bacterial vaccines; biofilm; bioluminescent imaging; Staphylococcus